Synthesis of Wavelength‐Shifting Fluorescent DNA and RNA with Two Photostable Cyanine–Styryl Dyes as the Base Surrogate Pair. Issue 4 (7th June 2017) - Steinmeyer, Jeannine; Rönicke, Franziska; Schepers, Ute; Wagenknecht, Hans‐Achim
Abstract: Two nucleic acid building blocks were synthesized, consisting of two photostable green‐ and red‐emitting cyanine–styryl dyes and ( S )‐3‐amino‐1, 2‐propanediol as a substitute for the ribofuranoside, and incorporated as base‐pair surrogates by using automated phosphoramidte chemistry in the solid phase. The optical properties and, in particular, the energy‐transfer properties were screened in a range of DNA duplexes, in which the "counter bases" of the two dyes were varied and the distance between the two dyes was enlarged to up to three intervening adenosine–thymidine pairs. The DNA duplex with the best optical properties and the best red/green emission ratio as the readout bore adenosine and thymidine opposite to the dyes, and the two dyes directly adjacent to each other as the base surrogate pair. This structural arrangement can be transferred to RNA to obtain similarly fluorescent RNA probes. Representatively, the positively evaluated DNA duplex was applied to verify the fluorescence readout in living HeLa cells by using fluorescence confocal microscopy. Abstract : DNA traffic lights : Two new DNA/RNA building blocks are synthesized and successfully incorporated into DNA and RNA by using automated solid‐phase chemistry. The two cyanine–styryl dyes, as base‐pair surrogates in DNA as well as in RNA, efficiently form an energy‐transfer pair. The energy transfer between dyes controls the color of the emission between red (double strand) and green (single strand), giving rise to promising tools for molecular imaging.